IT outsourcing opportunities in the Philippines - Abonal, Lalaine V. (Apples of Gold Pub., 2002)
A practical reference guide for public and private institutions who are looking for potential information technology (IT) service providers, suppliers of software and hardware peripheral equipments, organizers of international IT trade fairs, etc.